Transverse Testicular Ectopia: Two Case Reports - Tartar, Tugay; Sarac, Mehmet; Bakal, Unal; Canpolat, Senay; Kazez, Ahmet (Aves, 2018)
Transverse testicular ectopia (TTE) is a rare congenital anomaly caused by migration of the testes to the same half of the scrotum; it is associated with inguinal hernia. In addition, it is present along with persistent Mullerian duct syndrome (PMDS) in approximately 20% of patients. In such cases, Mullerian duct excision is recommended. In this article, we present two cases of TTE including one case of PMDS accompanied by TTE. Different approaches have been described in the treatment of TTE. Protection of testicular tissue and removal of the Mullerian duct, when TTE is present along with PMDS, are the basis of treatment.
Keywords: Transverse testicular ectopia; Persistent Mullerian duct syndrome; testis; surgery